(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The analysis of factors, trends and problematic situations of the development of Human Geography (a special discipline in the system of geographical science focused on the study of spatial determinants and patterns of development of society and its separate components and structures) in Russia in the XXI century is presented. Special attention is paid to the personnel of the Russian Human Geography and its localization. An inventory of priority areas of human-geographical analysis has been carried out. The most important scientific and scientific-practical achievements of Russian human geographers over the past three decades are shown. The problematic situations and barriers to further positive dynamics of research in the field of Human Geography in the Russian Federation are characterized and the tasks and directions for overcoming them are emphasized.